PERANCANGAN APLIKASI SISTEM MONITORING JARINGAN REMOTE PC BERBASIS JAVA - Desep Priandes; Ahmaddul Hadi; Dedy Irfan (Universitas Negeri Padang, 2017)
Utilization of information technology and computer network as data communication media until now increasing. The need for shared use of resources (Resources) that exist in the network both software and hardware has led to the emergence of various development of network technology itself. The bigger a company or institution that use computer network hence more complex also network system at company or agency, and needed a good handling for system can run optimally The purpose of this Final Project is to design and supervise the condition of computer and also Clientr on network And can handle it. The computer network administrator tasked with organizing and manag`ing the local network requires a lot of information, so that the decisions made lead to the best decision in handling the problems on a network. Therefore,management information on a network system will correctly affect the security of the network. After Implementation of Remote Access System Based on the test of software engineering laboratory obtained convenience Port used in the process of remote monitoring computer network on port 6060. So that it can be Implemented by computer users, in the process of Monitoring Remote Network Computer. Keywords : Remote Komputer, Java, Netbeans, Framework,Unified Modelling Language.